Islamic Populism and Village Chief Elections in Java - Cornelis Lay; Wegik Prasetyo; Norin Mustika Rahadiri Abheseka (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
The strengthening of political identities, including the use of Islamic populism, has widely been used to explain the electoral victories and defeats of candidates at the municipal, provincial, and national levels. However, no study has been found to investigate this phenomenon in the village elections (pilkades) of Yogyakarta, Indonesia. Our research, conducted in ten villages, did not find a tendency to use Islamic populism. Rather, in two villages—Baleharjo, Gunungkidul, and Temon Kulon, Kulon Progo—we identified an interesting phenomenon: the principle of inclusivity was used to ensure that competition was open to candidates of all backgrounds, including religious minorities. This article seeks to investigate this trend, which enabled religious minorities to be elected to the highest position within the village government: chief. It finds that minority candidates' electoral victory was made possible by several factors. Importantly, Islam's limited penetration into suburban Java restricted its ability to be used for identity politics in village elections.